City of shattered light - Winn, Claire (Flux, 2021)
Seventeen-year-old Asa flees her domineering father to prevent her sister's mind from being reprogrammed, but she must ally with a smuggler named Riven to outwit a bounty hunter, a criminal syndicate, and a monster lurking in the city's circuits.